Impact of ejaculation frequency on semen parameters and DNA fragmentation: a cross-sectional study - Qi Xi; Qingkuo Kong; Xin Lv; Rulin Dai; Yang Yu (Reproductive Biology and Endocrinology)
Abstract Background Abnormal sperm quality, particularly high sperm DNA fragmentation levels, is associated with infertility and a higher risk of pregnancy loss. While short abstinence periods may improve semen quality, the specific role of ejaculation frequency (EF) remains unclear. EF refers to the number of times an individual ejaculates within a given period, which is distinct from the abstinence period, defined as the time interval between ejaculations. This study investigates the association between EF and semen quality, including sperm DNA fragmentation. Methods This cross-sectional study included 1,349 men who underwent semen analysis at a reproductive center between November 2023 and July 2024. The subjects were categorized into three groups based on their self-reported EF over the past four weeks: EF1: <1/week, EF2: ≥1 and <2/week, and EF3: ≥2/week. Results As EF increased, significant decreases were observed in sperm DNA fragmentation index (DFI) (P < 0.001), semen volume (P = 0.012), sperm concentration (P < 0.001), and total sperm count (P < 0.001). Sperm vitality showed a positive association with EF (P < 0.001), while no association was found between sperm progressive motility and EF. Lower risks of elevated sperm DFI and necrozoospermia were observed in EF2 and EF3 compared to EF1. However, there was no increased risk of oligozoospermia or asthenozoospermia with increased EF. Conclusions Higher ejaculation frequency is associated with improved sperm vitality and lower DFI without negatively impacting motility. EF should be considered alongside abstinence in male fertility assessments. Trial registration The study was registered on ClinicalTrials.gov (identifier NCT06127875). Date of registration November 11th, 2023. Date of enrollment of the first subject: November 11th, 2023.